2022
DOI: 10.1186/s43019-022-00173-z
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track surgery and telerehabilitation protocol in unicompartmental knee arthroplasty leads to superior outcomes when compared with the standard protocol: a propensity-matched pilot study

Abstract: Background Several strategies have been devised to reduce the length of stay after orthopedic surgery. Telerehabilitation has proved effective in functional outcomes after orthopedic procedures and is appreciated by patients. There is limited information on fast-track surgery and telerehabilitation protocols for unicompartmental knee arthroplasty (UKA). The purpose of this pilot study was to report and compare functional outcomes and satisfaction levels during first 12 months of recovery in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Enoxaparin sodium 4000 units subcutaneously daily for 45 days was used as thromboembolic prophylaxis. The postoperative protocol was conducted following a previous report [12]. Briefly, both the patient groups followed the same study protocol involving passive mobilisation from day one after the surgery.…”
Section: Surgical Procedures and Rehabilitationmentioning
confidence: 99%
“…Enoxaparin sodium 4000 units subcutaneously daily for 45 days was used as thromboembolic prophylaxis. The postoperative protocol was conducted following a previous report [12]. Briefly, both the patient groups followed the same study protocol involving passive mobilisation from day one after the surgery.…”
Section: Surgical Procedures and Rehabilitationmentioning
confidence: 99%
“…Even though this latter study is outside of the Fast Track setting, and none of the above-mentioned studies use PSM to compare the procedures on the PROMs, the studies confirm the increasing adoption of bias-correcting techniques, such as PSM, to eliminate confounders in the comparison of cohorts of patients in orthopedic settings. As we mentioned in the introduction, only the recent study by De Berardinis et al [ 15 ], applied PSM to analyze the impact of the Fast Track on PROMs: in particular, the authors found that patients undergoing UKA, according to a fast-track and telerehabilitation protocol, had significantly better WOMAC index scores at 2, 15, and 40 days than those undergoing standard surgery and rehabilitation, using the PSM methods. When compared with this previous study, our results are more general in terms of the considered procedures (in that they apply to both hip- and knee-related procedures, rather than only knee-related ones), and also we consider the SF-12 scores, rather than WOMAC, which, as mentioned before, is one of the most common tools used to measure HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Care-as-Usual rehabilitation programs result in a longer delay between surgery and rehabilitation activities aimed at functional recovery, leading to delayed discharge, as well as complications associated with a longer hospital stay. Although [ 14 ] observed that supervised progressive resistance training was not superior when compared to unsupervised home-based exercise, in the rehabilitation of patients who have had unicompartmental knee arthroplasty (UKA), a recent study by [ 15 ] found that patients undergoing UKA, according to a Fast Track and telerehabilitation protocol, had significantly better WOMAC index scores at 2, 15, and 40 days than those undergoing standard surgery and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis was performed using Microsoft Excel (2019) in conjunction with the XLSTAT resource pack (XLSTAT Premium, Addinsoft, New York, NY, USA). A propensity-score-matching (PSM) analysis was employed to minimize variations in known covariates between the cohorts [ 49 ], since several retrospective arthroplasty studies have used this type of analysis to minimize selection bias [ 8 , 27 , 50 57 ]. The two patient groups were matched one-to-one by an optimal matching algorithm [ 58 ].…”
Section: Methodsmentioning
confidence: 99%